Scrub typhus associated with reactive arthritis: A case report and literature review - Shinya Yamanaka; Kazuhiro Ishikawa; Miyako Kon; Junko Aoki; Kunimichi Saeki; Junta Tanaka (IDCases)
Scrub typhus (tsutsugamushi disease) is an acute febrile illness caused by Orientia tsutsugamushi, often found in Asia and Oceania. The presence of an eschar, characterized by a crust, is a key diagnostic finding. Many symptoms of this disease are already known, however reactive arthritis following scrub typhus is very rare. Here, we present a case of 79-year-old man who was referred to our hospital because of continuous fever and left shoulder pain. We found 4-fold rise in Orientia tsutugamushi-specific IgG titer using paired serum samples and Orientia sp. genes by real-time PCR from a crust of right thigh. And the left shoulder joint image was consistent with aseptic arthritis; thus we diagnosed as scrub typhus with reactive arthritis. This case highlights the importance of recognizing reactive arthritis as a symptom of scrub typhus. In this report, we also review published cases of reactive arthritis associated with scrub typhus, and we suppose that this arthritis related to this infection may recover after antibiotic use and have a good prognosis. Physicians' awareness of newly appeared arthritis may contribute to facilitate early diagnosis, and may improve the course of such patients.